2019
DOI: 10.1038/s41556-018-0266-1
|View full text |Cite|
|
Sign up to set email alerts
|

SETDB1-mediated methylation of Akt promotes its K63-linked ubiquitination and activation leading to tumorigenesis

Abstract: The serine/threonine kinase Akt plays a central role in cell proliferation, survival and metabolism and its hyperactivation is linked to cancer progression. Here we report that Akt undergoes K64 methylation by SETDB1, which is crucial for cell membrane recruitment, phosphorylation and activation of Akt upon growth factor stimulation. Furthermore, we reveal an adaptor function of histone demethylase JMJD2A, which recognizes Akt K64 methylation and recruits E3 ligase TRAF6 and Skp2-SCF to the Akt complex, indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
135
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 138 publications
(150 citation statements)
references
References 37 publications
8
135
0
Order By: Relevance
“…For histology analysis, the tumors and tissues were fixed in 10% formalin, embedded in paraffin, sectioned and then performed hematoxylin and eosin (H&E) staining or immunohistochemistry staining by standard procedures 33 . The sectioned slides were antigen retrieved (0.01 M Citrate buffer, pH 6.0), incubated with the primary antibody for overnight at 4°C and then detected by VECTASTAIN Universal Quick HRP Kit (Peroxidase) (Vector Laboratory) with DAB kits (Abcam).…”
Section: Histology and Immunohistochemistrymentioning
confidence: 99%
“…For histology analysis, the tumors and tissues were fixed in 10% formalin, embedded in paraffin, sectioned and then performed hematoxylin and eosin (H&E) staining or immunohistochemistry staining by standard procedures 33 . The sectioned slides were antigen retrieved (0.01 M Citrate buffer, pH 6.0), incubated with the primary antibody for overnight at 4°C and then detected by VECTASTAIN Universal Quick HRP Kit (Peroxidase) (Vector Laboratory) with DAB kits (Abcam).…”
Section: Histology and Immunohistochemistrymentioning
confidence: 99%
“…The heterogeneity of the tumors, an incomplete understanding of HCC pathogenesis mechanism, and the lack of efficiency of targeted therapy limit the prognosis of HCC 6 . The occurrence and development of HCC is a complex process, including hepatocyte death, inflammation, fibrosis, cirrhosis, cycles of cell death and compensatory hepatocyte proliferation 7 . Thus, it is essential to underscore different intracellular signals of hepatocarcinogenesis and find multi‐targets active natural compounds to improve current HCC treatment modality.…”
Section: Introductionmentioning
confidence: 99%
“…7,9,15,16 In this study, the anomalous expression pattern of SKP2 in RB tissues and cell lines were observed. 7,9,15,16 In this study, the anomalous expression pattern of SKP2 in RB tissues and cell lines were observed.…”
Section: Discussionmentioning
confidence: 61%